Is sqrt{ (X- 3)^2 } = 3-X ? 1) X is not equal to 3 2) -X|X| : DS Archive
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 20 Jan 2017, 23:47

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Events & Promotions

Events & Promotions in June
Open Detailed Calendar

Is sqrt{ (X- 3)^2 } = 3-X ? 1) X is not equal to 3 2) -X|X|

Author Message
Senior Manager
Joined: 07 Mar 2006
Posts: 352
Followers: 1

Kudos [?]: 30 [0], given: 1

Is sqrt{ (X- 3)^2 } = 3-X ? 1) X is not equal to 3 2) -X|X| [#permalink]

Show Tags

30 Jul 2006, 03:58
00:00

Difficulty:

(N/A)

Question Stats:

0% (00:00) correct 0% (00:00) wrong based on 0 sessions

HideShow timer Statistics

This topic is locked. If you want to discuss this question please re-post it in the respective forum.

Is sqrt{ (X- 3)^2 } = 3-X ?

1) X is not equal to 3

2) -X|X| =0

(A) Statement (1) alone is sufficient, but statement (2) alone is not sufficient.
(B) Statement (2) alone is sufficient, but statement (1) alone is not sufficient.
(C) BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
(D) Each statement ALONE is sufficient.
(E) Statements (1) and (2) TOGETHER are NOT sufficient

My doubt:
Statement 1 should be sufficient on it's own since sqrt{ (X- 3)^2 } = 3-X
only when X =3.
Senior Manager
Joined: 19 Jul 2006
Posts: 361
Followers: 2

Kudos [?]: 6 [0], given: 0

Show Tags

30 Jul 2006, 07:20
sqrt{ (X- 3)^2 } = 3-X
=> + - (X- 3) = 3-X

Other then X=3, the above equation can statisy for infinite values.
depending on the sign of sqrt values.

Is it E ?
Senior Manager
Joined: 22 May 2006
Posts: 371
Location: Rancho Palos Verdes
Followers: 1

Kudos [?]: 110 [0], given: 0

Show Tags

30 Jul 2006, 07:33
given sqrt{ (X- 3)^2 } = |x-3|

S1 X!=3 insufficient. x-3 or -x+3
S2 X=0 sufficient
sqrt[(0- 3)^2] = 3

B it is.
_________________

The only thing that matters is what you believe.

Senior Manager
Joined: 14 Jul 2005
Posts: 402
Followers: 1

Kudos [?]: 27 [0], given: 0

Show Tags

30 Jul 2006, 08:11
I'll go with B on this one..

St1. x<>3 is insufficient
for x=1, equation is satisfied (1=1)
for x=4, equation is not satisfied (1=-1)

St2. -X|X| = 0 => X=0
Then sqrt{(0-3)^2} = 3-0 which is satisfied...
which is SUFF
Senior Manager
Joined: 07 Mar 2006
Posts: 352
Followers: 1

Kudos [?]: 30 [0], given: 1

Show Tags

30 Jul 2006, 09:37
The OA is B.
SVP
Joined: 30 Mar 2006
Posts: 1737
Followers: 1

Kudos [?]: 78 [0], given: 0

Show Tags

31 Jul 2006, 22:18
Clear B.

1) Sqr {(x-3)^2}

when x <0
Sqr {(x-3)^2} = -(x-3) = 3-x

When x > 0 and != 3
Sqr {(x-3)^2} != 3-x

Not Suff

2) -x|x| = 0

Means x = 0
Suff.
Manager
Joined: 25 Apr 2006
Posts: 50
Followers: 0

Kudos [?]: 2 [0], given: 0

Show Tags

05 Aug 2006, 06:03
zoom612 wrote:
Is sqrt{ (X- 3)^2 } = 3-X ?

1) X is not equal to 3

2) -X|X| =0

(A) Statement (1) alone is sufficient, but statement (2) alone is not sufficient.
(B) Statement (2) alone is sufficient, but statement (1) alone is not sufficient.
(C) BOTH statements TOGETHER are sufficient, but NEITHER statement ALONE is sufficient.
(D) Each statement ALONE is sufficient.
(E) Statements (1) and (2) TOGETHER are NOT sufficient

My doubt:
Statement 1 should be sufficient on it's own since sqrt{ (X- 3)^2 } = 3-X
only when X =3.

I am not clear on this. I think the answer is D

It is a yes/no question.

from stem the question is x-3 = 3-x?

From (1) since x!=3 we can answer a definite no the above question. Whether 3 is negative or positive or 0, as long it is not 3, the LHS will be -1 times RHS. So, SUFF

From (2) x=0. So the question turns out to is -3=3 and again the answer is no in this case. So, SUFF.

Where am I going wrong here. Can anyone please explain?

Thanks.
Manager
Joined: 20 Mar 2006
Posts: 200
Followers: 1

Kudos [?]: 3 [0], given: 0

Show Tags

05 Aug 2006, 12:57
sqrt{ (X- 3)^2 } = |x-3|
If x>= 3 , |x-3| = x-3
If x< 3, |x-3| = 3-x

1) x not equal to 3
|x-3| = x-3 for x>3
|x-3| = 3-x for x<3
Insuff

2) -X|X| =0
since |x| is always +ve
-x = 0
i.e x = 0
therfore x<3 implies |x-3| = 3-x
Suff

Hence B

Heman
Manager
Joined: 25 Apr 2006
Posts: 50
Followers: 0

Kudos [?]: 2 [0], given: 0

Show Tags

05 Aug 2006, 13:39
heman wrote:
sqrt{ (X- 3)^2 } = |x-3|
If x>= 3 , |x-3| = x-3
If x< 3, |x-3| = 3-x

1) x not equal to 3
|x-3| = x-3 for x>3
|x-3| = 3-x for x<3
Insuff

2) -X|X| =0
since |x| is always +ve
-x = 0
i.e x = 0
therfore x<3 implies |x-3| = 3-x
Suff

Hence B

Heman

But sqrt { (x-3) ^2} is a radical. In that case only positive value can be taken. So, its just (x-3) and not (3-x). Am I not correct?
Manager
Joined: 20 Mar 2006
Posts: 200
Followers: 1

Kudos [?]: 3 [0], given: 0

Show Tags

05 Aug 2006, 14:08
yessuresh wrote:
heman wrote:
sqrt{ (X- 3)^2 } = |x-3|
Hence B

Heman

But sqrt { (x-3) ^2} is a radical. In that case only positive value can be taken. So, its just (x-3) and not (3-x). Am I not correct?

Why dont you take examples
(1) When x>3 for eg x=4 then |x-3| = x-3
Lhs = 1 Rhs = -1 Not Equal --> No

When x<3 for eg x=2 then |x-3| = 3-x
Lhs = 1 Rhs = 1 Yes

So you get a Yes and a No for statement (1) hence insufficient

Hope that is clear

Heman
Re: DS: Gmat prep   [#permalink] 05 Aug 2006, 14:08
Display posts from previous: Sort by